Analisis SWOT Sebagai Strategi Pengembangan UMKM (Studi Kasus pada Pecel Blitar & Rawon Mbak Dwi di Sengkaling Kabupaten Malang) - Salsabila Rahmantia Sumartuti; Joko Samboro; Ita Rifiani Permatasari (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
Pecel Blitar and Rawon Mbak Dwi is a culinary business that has been operating for ten years. Despite its longevity, the business currently faces challenges in maintaining sustainability and achieving growth in an increasingly competitive market. To address these challenges, it is essential to continuously analyze both the internal and external business environtments (SWOT). This study aims to analyze / identify internal and external factors and develop strategic recommendations through SWOT analysis. This research employed qualitative method. Primary data were collected through in-depth interviews with selected informants. The data collection techniques included observation and documentation. SWOT analysis was used to assess the internal & external environment and to formulate strategic business development strategies alternatives. The analysis involved identifying strengths, weaknesses, opportunities, and threats, followed by weighting, rating, and scoring using the IFAS and EFAS matrices.The research identified six strength factors, six weaknesses factors, five opportunity factors, and five threat factors. Based on the SWOT analysis, the IFAS matrix yielded a score of 2,83, while the EFAS matrix yielded a score of 3,22, placing the business in SWOT Quadran I, which indicated strong strengths and opportunities. The recommended strategy was the SO strategy, including product variation with affordable pricing.  The study concluded that Pecel Blitar & Rawon Mbak Dwi leveraged its strengths and opportunities to enhance business performance. It is recommended that Pecel Blitar & Rawon Mbak Dwi should be able to innovate products and optimize marketing strategies through social media.